Pulmonary nocardiosis: Report of two cases from a tertiary care hospital - Archana Baburao; Sruthi Prasad; S Prakash; Huliraj Narayanswamy (Wolters Kluwer Medknow Publications, 2019)
Pulmonary nocardiosis is an uncommon bacterial infection that may lead to severe disease in immunocompromised patients. The disease is rare in immunocompetent patients. Reported cases are few, and the literature is limited because disease recognition is difficult. We present a case report of two patients of pulmonary nocardiosis, who had different clinicoradiological presentations and also responded differently to treatment. Given the rising incidence of cancer, organ transplantation, and use of parenteral steroids, Nocardia is likely to attain a higher place among the causes of pulmonary infections.